The Rise, Fall, and Rethink of (Fluoro)quinolones: A Quick Rundown - Célia Fortuna Rodrigues; Francisco Silva (Pathogens)
Antibiotics have revolutionized medicine, with (fluoro)quinolones emerging as one of the most impactful classes of antibacterial agents. Since their introduction, four generations of (fluoro)quinolones have been developed, demonstrating a broad spectrum of activity, favourable pharmacokinetics, and clinical efficacy. However, the rise of multidrug-resistant pathogens has posed significant challenges to their continued effectiveness, particularly in healthcare settings. Among the main resistant species, Staphylococcus aureus, particularly methicillin-resistant strains (MRSA), Klebsiella pneumoniae, Enterococcus spp. (E. faecium and E. faecalis), Campylobacter spp., and Acinetobacter baumannii are the most important. This critical literature review provides an updated perspective on (fluoro)quinolones (old and new), encompassing their spectrum of activity, pharmacokinetics, mechanisms of resistance, and the role of antimicrobial stewardship in preserving their utility, to address the growing threat of resistance.